Game-Based Training to Promote Arithmetic Fluency - Jay, Tim; Habgood, Jake; Mees, Martyn; Howard-Jones, Paul (Frontiers in Education, 2019)
The research team designed and evaluated a mobile game to promote rapid retrieval of arithmetic facts among a group of children aged 7-8 years (n=97). The design of the game was based on principles drawn from research literature in mathematical cognition, game-based learning, and game design. The game trains basic number knowledge within a motivating context. It tested an implication of theory of automatization of arithmetic facts that training of recognition of multiples of single-digit numbers should lead to greater fluency in solving multiplication and division problems. A quasi-experimental design was employed to test whether the game improves retrieval of arithmetic facts. Children played the game in their classrooms for 20 minutes a day for 2 weeks. Comparisons between pre- and post-tests showed that the game playing group outperformed controls with a medium to large effect size (> 0.6). These results suggest an improvement in arithmetic fluency equivalent to around 7 months’ progress and provide rare empirical evidence supporting transfer of game-based training to a pencil-and-paper test. The findings are consistent with a connectionist theory of arithmetic skill, by showing that improved recognition of multiples contributes to multiplication and division skill. The theoretical and practical implications of these findings are discussed.